Look up! : bird-watching in your own backyard - Cate, Annette (Somerville, Massachusetts : Candlewick Press, 2019)
Children's book describing bird-watching tools and techniques.
Ages 8-12.
"Bonus! 18 pages of new bird-watching activities and tips"--Cover.
Some pages lack numbering.
Includes bibliographical references (page 52) and index.
Keywords: Bird watching -- Juvenile literature; Birds -- Identification -- Juvenile literature; Bird watching; Birds; Field guides; Juvenile works